Volatile components of raw Patin Catfish (Pangasius hypophthalmus) and Nile Tilapia (Oreochromis niloticus). (July 2018) - Pratama, Rusky I; Rostini, I; Lviawaty, E
Abstract: Volatile components are groups of compounds which could affect the aroma and acceptance of commodities. The objective of this research was to identify volatile components of two most common freshwater commodities in Indonesia which are patin catfish ( Pangasius hypophthalmus ) and nile tilapia ( Oreochromis niloticus). The method used in this study were to detect volatile compounds using Gas Chromatography/Mass Spectrometry (GC/MS) on both fresh fish samples with Solid Phase Micro Extraction (SPME) as an initial extraction method. The volatile components analysis successfully detects and identify as many as 46 volatiles compounds in raw nile tilapia and 59 compounds were detected in raw patin catfish. Most of the detected components came from hydrocarbons, aldehydes, alcohols and ketone groups. Most of those volatile compounds detected were derived from the results of enzymatic reactions, lipid auto oxidation and various environmental influences.